ХУДОЖЕСТВЕННЫЕ ПРОИЗВЕДЕНИЯ В АЗЕРБАЙДЖАНСКОЙ ЛИТЕРАТУРЕ, ПОСВЯЩЕННЫЕ ИМАДЕДДИНУ НАСИМИ - Пюста Ахмедова (International Journal of Innovative Technologies in Social Science, 2020)
As a result of attention and interest to the heritage of Imadaddin Nasimi, the great thinker of the 14th century, numerous works of various genres have been written about the life and creativity of Nasimi. Each of the lyrical, epic and dramatic works dedicated to Imadaddin Nasimi are referred to his creativity and destiny. Reflecting the artistic and philosophical world of Nasimi, it becomes clear from each of these works that Nasimi is one of the greatest literary figures not only of his time, but of Azerbaijani literature as a whole. Other authors such as Islam Safarli, Rasul Rza, Aliagha Kurchayli, Nabi Khazri, Bakhtiyar Vahabzade, Isa Huseynov, Mahmud Ismayil, Ali Tuda, Sohrab Tahir, Jabir Novruz, Qabil, Khalil Rza Uluturk, Fikret Sadig, Kalantar Kalantarli, Isa Ismayilzadeh, Mammad Ismayil, Musa Yagub, Alakbar Salahzadeh who covered the poet's difficult life path, wrote about Nasimi and his time, they turned to the artist's creativity as a primary source, as a result, presented literary works that fully cover the poet's creativity and biography.In each of these works based on the historical principles and dedicated to Nasimi, Nasimi's poetry was analyzed and approached in the context of the period in which it was written. Each of these works is a literary example that gives a full idea of the poet's life and art.